MANAGEMENT OF PANGSAN TOURISM VILLAGE AS A TOURISM DESTINATION BASED ON TRI HITA KARANA - Ni Ketut Suardani (UHN IGB Sugriwa Denpasar, 2025)
A tourist village is an area consisting of local communities who interact in tourism management, with the aim of increasing the community's role in increasing tourism potential in each village area. Pangsan Tourism Village is one of the promising tourist destinations in North Badung, but it needs better and more effective management. This research examines the potential of Pangsan Tourism Village as a Tri Hita Karana-based tourist destination, its management efforts, and the obstacles that still exist. This research uses qualitative research methods with descriptive analysis techniques. The research results show that Pangsan Tourism Village has a variety of natural, cultural and artificial potential. Pangsan Tourism Village management efforts have been quite good in providing facilities and access, but deficiencies are still found in supporting facilities and additional services. The obstacles found were less than optimal planning and design of tourism packages, low community involvement, and a lack of understanding of the Pangsan Tourism Village management. Therefore, Pangsan Tourism Village needs to improve supporting facilities, partner with travel agents, and provide further assistance to optimize management.